(untitled) (Collection of scientific works «Modern structures of metal and wood», 2020)
This article discusses the issues of practical probability calculation of failure-free operation of quasihomogeneous bolted joints of steel silo body sheets. The heterogeneity of the joints of silo thin-sheet structures can be caused by a number of reasons, the most common of which are installation errors, for example, the presence of a beyond-design strength class in the bolt joint. Such a defect will cause an increase in the risk of failure, to quantify the value of which is not possible, according to existing engineering methods or guidelines of regulatory documents. It is more logical in this direction to use probabilistic methods of calculation, which, firstly, give a more justified economic result, and secondly, depending on the adopted indicator, can be a qualitative and quantitative characteristic of any parameter. As part of this problem, the reliability calculation of the joint was performed by determining a random value of the critical variable coefficient. The value of this parameter was taken equal to the ratio of the random value of the generalized stress to the random value of the joint bearing capacity. In the presented example of a bolted joint of thin- sheet silo structures, the critical variable coefficient was determined according to the author’s technique from a system of conditions under which the reliability of an inhomogeneous joint is observed. The article also investigated the dependence of the level of joint reliability when varying the number of beyond-design bolts. The results of changes in the probability of failure-free operation and the behavior of the reliability graphs are illustrated in the graphs as a set of critical variable curves on a critical probability scale. The choice of this visualization is based on the simplicity and clarity of the presentation of the results received. The study showed that with a small number of “replacement” bolts, they are the main reason for the failure of the joint; however, with an increase in the number of beyond-design bolts, the fracture mechanism will depend on the probabilistic justification of the load and strength.